The People of the River : Nature and Identity in Black Amazonia, 1835-1945 - De la Torre, Oscar (Historian) (Book collections on Project MUSE., 2018)
"In this history of the black peasants of Amazonia, Oscar de la Torre focuses on the experience of African-descended people navigating the transition from slavery to freedom. Drawing on social and environmental history, he connects the Amazonians intimately to their natural landscapes. Relying on the natural world as a repository for traditions, discourses, and strategies that they retrieved especially in moments of conflict, Afro-Brazilians fought for autonomous communities and developed a vibrant ethnic identity that supported their struggles over labor, land, and citizenship."--